EXPERIMENTAL AND NUMERICAL MODELING OF THE METASOMATIC REPLACEMENT OF PICROILMENITES FROM KIMBERLITES - Lashkevich V.V.; Medvedev V.Ya.; Egorov K.N.; Ivanova L.A. (My University, 2004)
The formation of a reaction rim around picroilmenite from kimberlite was studied by means of experimental and numerical modeling. em. The replacement of picroilmenite gave rise to chemical zoning in the ilmenite matrix (from core to rim): (1) a decrease of TiO2 and FeO; and (2) a sharp increase of Fe2O3, Al 2O3, MgO, and Cr2O3. The synthesized reaction rims of picroilmenite mainly consist of perovskite and titanomagnetite. Numerical modeling with the Selector program revealed the effect of fluid composition and redox conditions on the formation of polymineral reaction rims. The numerical modeling of the replacement of picroilmenite is consistent with experimental data.